Theology and ethics for the public church : mission in the 21st century world - Samuel Yonas Deressa; Dreier, Mary Sue Dehmlow., 1951- (Lanham : : Lexington Books, Fortress Academic, 2023)
"Drawing upon the public theology of Gary M. Simpson and personal experiences, contributors provide theological perspectives on the ethics and opportunities of twenty-first century Christian mission and envision promising pathways for Christian congregations to faithfully bear social responsibility in contemporary worldwide contexts"--
Includes bibliographical references and index.
Keywords: Public theology; Religious ethics; Theology of the cross; Mission of the church; Responsibility -- Religious aspects -- Christianity